Um projeto de cidadania feminina negra parlamentar e a violência política interseccional de gênero e raça - Machado, Fabiana de Jezus (Universidade Federal de São Carlos, 2026)
The phenomenon of gender and race-based political violence has been widely examined in academic research that seeks to reflect on the limits and challenges of a project of Afro Brazilian female parliament citizenship. Understood as a manifestation of a political institutional system structured under the aegis of sexism and misogynistic culture, this form of violence effectively excludes Afro American women from the right to participate in political life by failing to recognize the political sphere as a legitimate space for women’s participation. In this sense, the present study aims to reflect on the Relationship between the political participation of Afro Brazilian women in institutional politics and the intersectional political violence of gender and race. The theoretical framework underpinning this reflection draws on Afro Brazilian feminism epistemologies, particularly the concept of the raciality dispositif, coined by Sueli Carneiro. The problematization of this research is linked to the approval by the Brazilian National Congress of Constitutional Amendment nº 133/2024, which granted amnesty for fines imposed on political parties that failed to comply with gender and racial quota requirements in electoral processes. The documentary research was conducted through the analysis of official documents and data collected by the Observatory of Whiteness, affiliated with the Institute of Socioeconomic Studies, as well as data from the Brazilian Superior Electoral Court regarding candidacies and elected mandates in the 2024 electoral cycle in the state of São Paulo. Based on the analysis of these data, the study seeks to demonstrate that Constitutional Amendment nº 133/2024 operates as a raciality dispositif and can therefore be understood as one of the dimensions of gender and race-based political violence. This violence is perpetrated by the State itself, contributing to the reproduction of the logic that sustains male and white dominance in Brazilian political Spaces, while simultaneously restricting Afro american women’s access to decision-making positions of power. Key-words: Political Violence Based on Gender and Race; Structural Racism; Political Participation; Raciality Dispositif.
A project on black womens parliamentary citizenship and the intersectional political violence of gender and race
Keywords: Violência política de gênero e raça; Parlamentares negras; Interseccionalidade; Dispositivo de racialidade; Political violence based on gender and race; Structural racism; Political participation; Raciality dispositif; CIENCIAS HUMANAS; 5. Igualdade de Gênero